Optical active centres in ZnO samples - Monteiro, T. (2006)
In recent years, there has been a resurgence in the interest in the use of ZnO (Eg ∼ 3.37 eV) as a material for a wide range of opto-emitter applications spanning visible and short wavelengths. Bulk, thin films and nanomaterials obtained using different synthesis methods have been investigated for optoelectronic and biotechnological device applications. Nominally undoped bulk samples typically present a myriad-structured near-band-edge recombination, mainly due to free/bound excitons and donor–acceptor pair transitions. Furthermore, deep level emission due to intrinsic defects and extrinsic impurities, such as transition metal ions, are commonly observed in different grades of bulk ZnO samples. Undoped thin film and ZnO nanocrystal samples also present optically-active centres due to the presence of native and extrinsic defects. Continuing improvement in device performance hinges on improved understanding of the role of these defects present in ZnO samples. In this work a correlation between the optical centres was observed between nominally-undoped bulk, thin films and nanocrystal ZnO. We also observed a correlation between the structural properties and ion optical activation for single crystal samples which were intentionally-doped with rare earth ions (Tm, Er, Eu and Tb) either (a) by ion-implantation or (b) during synthesis. For the doped ZnO nanocrystals, intra-ionic recombination and XRD data suggest that the ions are in a crystalline environment.